China-Kenya Relations: Analysis of the Kenyan News Discourse - Vilém Řehák (Modern Africa, 2016)
Although virtually all states in the world adhere to market economy, they have different visions about how the market economy should work properly. We may identify three main ideal-typical models of market state, welfare state, and developmental state, which are in practice realised by the US, the EU, and Pacific Asia. These ideas about global economy serve as strategic narratives, which are formed within the respective regions, projected into other regions, and received in these other regions. The reception of narratives, particularly by ordinary people, has attracted scholarly attention only very recently and still remains under-studied. This article focuses on the reception of the Chinese narrative towards Africa, which stresses a win-win cooperation based on the “business as usual” approach, with no political interference and no strings attached. Kenya was chosen as a representative case, the discourse analysis of media news discourse as a method, and the leading newspaper The Daily Nation as the source of data. The analysis reveals that the newspaper reproduces this Chinese narrative, while simultaneously challenging it. At least two main constituent parts of this narrative are openly contested on the pages of The Daily Nation: that the Chinese aid to Africa is without conditions and that the Chinese engagement in Africa is selfless and mutually beneficial. Thus, the present article confirms that while Kenyan leadership seems to be charmed by the Chinese narrative, this is not accepted unreservedly within Kenyan society.